Clinical and radiological results of surgically treated patients with adolescent idiopathic scoliosis and the effects of pulmonary rehabilitation on respiration functions. Issue 7 (19th February 2021) - Dogar, Fatih; Argun, Mahmut; Erdem, Sevki; Gurbuz, Kaan; Argun, Ali Saltuk; Kafadar, Ibrahim Halil
Abstract: Background: In the present study, we aimed to evaluate the effects of pulmonary rehabilitation on respiratory functions after the surgery on the basis of early radiological findings, pain degree, function, and satisfaction scores in operated patients with adolescent idiopathic scoliosis (AIS). Methods: Thirty patients with AIS were included in the present study, who were divided into 2 groups. Scoliosis surgery and diaphragmatic breathing and pursed lip exercises were applied in Group 1 (n = 15), whereas merely scoliosis surgery was applied in Group 2 (n = 15). Pulmonary functions, arterial blood gas analysis, Cobb and kyphosis angles, apical vertebral rotation, and apical vertebral translation were measured before and 1st and 6th months after the surgery. Using the SRS-30 test, the psychosocial statuses of the patients and their satisfaction degrees with surgery applied were measured before and after the surgery. Results: Six months after the surgery, the values of Cobb and kyphosis angles and apical vertebral rotations, and apical vertebral translation of the patients were determined to be significantly ameliorated, which is consistent with the literature. Forced vital capacity (l) and forced expiratory volume in the first second (l/s) were observed to be significantly improved in both groups after the surgery (respectively, P  = .001, P  = .014, P  = .001, P  = .005). In addition, the partial pressure of oxygen (pO2 ) value was found to be significantly increased 6 months after the surgery compared with that before the surgery in Group 2 ( P  = .022). SRS-30 showed that most of the scores in Group 1 were dramatically increased; a significant difference between the groups was not recorded. Conclusion: Patients with AIS have been found to be satisfied with the surgery. Conversely, pulmonary rehabilitation has been shown to slightly improve the respiratory functions in the patients with AIS, 1 and 6 months after the surgery.